Vozes feministas em rede: um estudo sobre campanhas femvertising no Instagram - Figueiredo, Carla (2025)
To amplify and make audible feminine and feminist voices that reverberate through social networks, the present study investigates the disputes over meanings surrounding contemporary feminisms, based on the femvertising campaigns “I am a woman, and it is obvious that …” and “The Dove Code”. This analysis draws upon Fraser’s (2006, 2024) conceptualization of the bidimensional dialectic of recognition and redistribution of gender injustices, complemented by Banet-Weiser’s (2012, 2018) theorization on the ambivalence of brand culture, which engenders tensions surrounding popular feminism. The research examines how femvertising plays a critical role in the circulation and interpretation of discourses that shape the symbolic values of feminisms as perceived by Brazilian women on Instagram. To this end, a multi-methodological approach was structured in three complementary cycles. A systematic literature review uncovered a preponderance of content producers’ perspectives as a predominant approach to femvertising studies in Brazil. Built upon the understanding of consumption as a symbolic practice (Douglas; Isherwood, 2004) and framing advertising and brands as symbolic and cultural artifacts (Perez, 2016; Trindade; Perez, 2014; Trindade, 2008, 2019), an exploratory research, anchored on Bardin’s (1977) content analysis method, was conducted to examine 533 comments on the campaign “I am a woman, and it is obvious that …”. The study unveiled the contributive yet commodified ambiguity of popular feminism (Banet-Weiser, 2018). Subsequently, the hybridization of social network analysis (SNA), operating under the quantitative framework proposed by Recuero, Bastos, and Zago (2020), in conjunction with Bardin’s (1977) content analysis, enabled the mapping of interactions and media actors in “The Dove Code” campaign, the processing of substantial data volumes, the construction of a thematic-ideological map, and the qualitative examination of 1,500 comments. The findings suggest that feminist demands are ambivalently amplified yet deprived of transformative social potential when voiced by influencers, to an even greater extent than by the brand itself. The study concludes that femvertising simultaneously operates as a vector of visibility and popularization of feminist agendas (Banet-Weiser, 2018) and as a pedagogical and commodifying device, both of which are operative in commodity feminism as revealed by Barreto Januário (2021, 2022). In this scenario, critical yet necessary paths emerge for future reception studies at the intersection of feminism and advertising, since this convergence addresses the symbolic dimension of recognition without effectively confronting the market, capitalist, and hegemonic mechanisms that underpin redistributive injustices, as argued by Fraser (2017).